Seasonal Reproductive Dynamics of a Lek-Breeding Neotropical Treefrog is not Organized by Male Size (Anura, Hylidae ) - Leao Pompeu, Caio Carneiro [UNESP]; Sa, Fabio P. de [UNESP]; Haddad, Celio F. B. [UNESP] (Soc Brasileira Herpetologia, 2020)
Social structure in anurans is directly related to reproductive traits such as chorus organization, male territoriality, pair formation, breeding site choice, and temporal breeding pattern. The Neotropical treefrog Dendropsophus sanborni is an excellent model for studies on reproductive dynamics because it is a prolonged-breeder and usually occurs in high densities. Here, our goals were to better understand the factors that lead to social organization and influence seasonal reproductive dynamics of males of the species. We addressed the hypotheses that (1) the seasonal dynamics of D. sanborni is locally delimited by climatic conditions throughout its breeding season and (2) territorial males are structured spatially and temporally based on body size. We carried out monthly field sampling between October 2015 and September 2016 in an ecotone region of Brazil that originally comprised Semideciduous Seasonal Forest and Cerrado (savannah vegetation). We specifically analyzed environmental conditions, population abundance, size of calling males, and microhabitat use. Our results showed that environmental conditions drive the seasonal reproductive pattern and social structure of calling males is not organized by size. We did not find significant variation in male size among months of the breeding season or among perch heights and types. Our findings suggest a prolonged seasonal reproductive pattern associated with climatic factors without a social structure based on body size.
Keywords: Anura; Breedingrecruitment; Breeding season; Dendropsophus sanborni; Socialorganization; Social structure; Atlantic Forest; Cerrado